Mandating the measurement of fraud : legislating against loss - Tunley, Martin; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This project examines the concept of fraud loss measurement by critiquing existing measurement methodologies, and argues for the mandating of fraud loss measurement by enforced self regulation, the creation of a British Standard of fraud loss measurement, and the establishment of an information exchange matrix to develop best practice.
Keywords: Fraud -- Law and legislation -- Great Britain; Forensic accounting -- Law and legislation -- Great Britain; Forensic accounting -- Great Britain; Business losses -- Great Britain